Normative Reference Values and Validity for the 30-Second Chair-Stand Test in Healthy Young Adults - Donald H. Lein Jr.; Mansour Alotaibi; Marzouq Almutairi; Harshvardhan Singh (International Journal of Sports Physical Therapy)
# Background